Identifying Factors Influencing the Number of Diarrhea Cases in Children Under Five in West Java Using Negative Binomial Regression - Akbar Rizki; Utami Dyah Syafitri; Christin Halim (Jurnal Matematika Sains dan Teknologi, 2024)
The WHO states that diarrhea is the leading killer of children under five worldwide, and Indonesia is no exception, where 10.3% of under-five deaths are caused by diarrhea. West Java Province, with the largest population in Indonesia, has the highest diarrhea cases under five. The potential for diarrhea to become an extraordinary event, which is often accompanied by death, is very likely to occur because diarrhea is an endemic disease in West Java. Therefore, analyzing the factors influencing the children under five diarrhea cases in West Java is essential. Negative binomial regression was used in this study because the response was to count data on the incidence of diarrhea in children under five in West Java. The analysis results show that an increase in the percentage of public premises (PPP) meeting health requirements and population density per km2 will increase the number of diarrhea cases under five in West Java. However, an increase in the percentage of Community-Based Total Sanitation (CBTS), percentage of the population living in poverty, and percentage of households practicing Clean and Healthy Behavior (CHB) will decrease the number of diarrhea cases in West Java.